2009
DOI: 10.3748/wjg.15.3771
|View full text |Cite
|
Sign up to set email alerts
|

No association between phosphatase and tensin homolog genetic polymorphisms and colon cancer

Abstract: AIM:To investigate the association between single nucleotide polymorphisms (SNPs) in the phosphatase and tensin homolog (PTEN) tumor suppressor gene and risk of colon cancer. METHODS:We utilized a population-based casecontrol study of incident colon cancer individuals (n = 421) and controls (n = 483) aged ≥ 30 years to conduct a comprehensive tagSNP association analysis of the PTEN gene. RESULTS:None of the PTEN SNPs were statistically significantly associated with colon cancer when control led for age, gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…Association studies for some of these polymorphisms have been reported previously. [14][15][16][17][18] Primers for polymerase chain reaction (PCR) were designed by Sequenom MassARRAY Assay Design 3.0 (Sequenom, San Diego, CA, USA).…”
Section: Snp Site Selection and Primer Designmentioning
confidence: 99%
“…Association studies for some of these polymorphisms have been reported previously. [14][15][16][17][18] Primers for polymerase chain reaction (PCR) were designed by Sequenom MassARRAY Assay Design 3.0 (Sequenom, San Diego, CA, USA).…”
Section: Snp Site Selection and Primer Designmentioning
confidence: 99%
“…Si le risque néoplasique digestif ne semble pas paradoxalement augmenté [12], une surveillance endoscopique tous les 3 à 5 ans à partir de 30 ans est préconisée [13].…”
Section: B) Lésions Muqueusesunclassified
“…In contrast, there is considerable evidence suggesting that Pten may not be directly associated with tumorigenesis in the colon. A study examining single nucleotide polymorphisms (SNPs) in the Pten gene indicated that there may be no association between Pten and colon cancer in humans [18]. Furthermore, the Pten mRNA level is not consistent among colorectal cancer tissues and varies depending on tumor location [19], and Pten mRNA expression was seen to be preserved in human colorectal adenomas and adenocarcinomas [20].…”
Section: Introductionmentioning
confidence: 99%